Does urban green space justly improve public health and well-being? A case study of Tianjin, a megacity in China. (20th December 2022) - Yang, He; Chen, Tianyu; Zeng, Zhi; Mi, Feng
Abstract: Urban green space (UGS) planning and design can not only influence economic development and the ecological environment but also have a significant impact on urban public health. Facing the increasingly serious public health crisis in megacities, promoting environmental justice in UGS, and improving the health and well-being of urban residents have become critical issues to be addressed in response to the global urban sustainable development goals (SDGs). Using data from a survey of 682 residents in the central district of Tianjin, we constructed a structural equation model based on theoretical analyses of spatial justice, social stratification, and Rawls' theory to reveal injustices in the accessibility of health benefits of UGS among residents of different socioeconomic status (SES) and explore the ways in which SES affects residents' health and well-being via UGS. The results indicate that: (1) Increasing the intensity of green space exposure can improve residents' health and well-being, but due to the urban green space premium effect, inequities exist among residents of different SES in enjoying the health benefits of UGS, thus deepening health inequality in megacities. (2) SES can influence residents' health and well-being through three paths: "green premium mechanism", "green exposure mechanism", and "green chain mechanism", and green space premium and green space exposure play a mediating role in the influence of SES on residents' health and well-being. (3) To promote environmental justice in UGS, provide urban human care, and guarantee public health equality, the UGS in China's megacities needs to be further explored in terms of UGS layout optimization, service quality improvement, and management system guarantee.